The Andean Community Law - Chanamé Orbe, Raúl (2022)
Within the integration processes in the world, it is necessary to remark the experience of the integration process that has happened in our region since the subscription of CartagenaAgreement (May 26th of 1969), that in it’s institutional evolution in the last five decades has created a regulatory system own to its history , practices and organization called Andean Community Law, which has manifested in the Andean Integration System through political, legal, parliamentary, economic, educational, migratory, sanitary and industrial agreements for the benefit of its members.